Implementing the Wireless FTT Protocol: A Feasibility Analysis - Bartolomeu, Paulo
Low-power wireless communication protocols have been shown to experience a significant timeliness and reliability degradation under certain interference profiles. Provided that this impairment has hindered their wide adoption in demanding real-time scenarios, the Wireless Flexible Time Triggered (WFTT) protocol has been recently proposed targeting applications with stringent timeliness requirements. This protocol builds on the medium access determinism granted by the bandjacking technique in open environments, where different technologies may contend for the medium. Besides providing a deeper definition of the WFTT architecture and protocol operation, this paper presents a thorough analysis addressing its implementation feasibility.